Empowerment of Cash Waqf in the Agricultural Sector - Johari Johari (Proceeding of The International Conference on Economics and Business, 2022)
Waqf has become the world's attention because this instrument can be utilized as a solution to world crisis problems. One of the countries with the most significant potential for waqf is Indonesia, which is based on a large number of followers of Islam. The number of adherents of Islam in Indonesia alone reaches 209.1 million adherents of Islam and makes the potential for Indonesian waqf very large. This type of research is descriptive qualitative, using the case research method and collecting data in this study through observation and in-depth interviews with research objects. The technique used in this research is critical and interpretative analysis. Cash waqf can be distributed to beneficiaries for business capital in the agricultural sector as a family food security distribution scheme with several models: first, a profit-sharing method (Mudharabah). Second, a 0% loan (Qard Hasan)"; third, business strengthening (Musyarakah); fourth, alms and grants (khairiyah). The agricultural system is developed into a culture for every family to become food security by implementing an integrated farming system. Agricultural system, "low external input and sustainable agriculture," at home and group/production scale. With this system and a touch of technology, the future is projected as a comprehensive agricultural center. Production and marketing are carried out simultaneously by building an "agricultural industry" and an "agricultural market." Apart from that, it can also be used as an educational, tourism, and cultural village. The academic village is intended as a research and training/educational practicum place. The tourism village is defined as agro-tourism which has high economic value